Are Health Literacy and Patient Activation Related to Health Outcomes in Breast Cancer Patients? - Chisom Kanu; Carolyn M. Brown; Karen Rascati; Leticia R. Moczygemba; Michael Mackert; Lalan Wilfong (SLACK Incorporated, 2021)
Background: Assessing health literacy and patient activation at the beginning of care could facilitate the provision of appropriate information to patients with breast cancer and increase the effectiveness of interventions geared toward improving patient involvement in self-managing their health and, consequently, their quality of life. Objective: The aim of this study was to evaluate cancer health literacy and patient activation in patients with breast cancer as well as examine their relationships to health-related quality of life (HRQoL) and resource use. Methods: Patients with breast cancer positive for human epidermal growth factor receptor 2 (HER2+) receiving care at 12 oncology clinics in Texas were offered participation in the study via convenience sampling. The survey consisted of the 6-item Cancer Health Literacy Tool, the 13-item Patient Activation Measure, the 27-item Functional Assessment of Cancer Therapy - General (version 4), and single-item measures for number of emergency department visits and hospitalizations as well as clinical and demographic characteristics. Key Results: The mean age of the 146 study participants was 57.1 ± 10.8 years; 92% (n = 134) had a high probability (≥0.7) of adequate cancer health literacy whereas 68% percent (n = 99) had high patient activation (level 3 or 4). Cancer health literacy had significant positive relationships with education and household income. Patient activation, education, and number of treatment types received explained 23% of the variation in HRQoL, and all except cancer health literacy were positive and significant predictors. No bivariate/multivariate analysis was conducted for emergency department visits and hospitalizations because there were few reported incidents. Conclusions: Interventions that aim to improve HRQoL in patients with breast cancer could target modifiable factors like patient activation. The homogeneity of cancer health literacy among study participants might have influenced its nonsignificant relationship with HRQoL and patient activation. Further assessments of health literacy and patient activation in larger and more diverse populations of patients with breast cancer are warranted. [HLRP: Health Literacy Research and Practice. 2021;5(3):e171-e178.] Plain Language Summary: In this study, the majority of patients with breast cancer were found to have high levels of cancer health literacy, patient activation, and health-related quality of life (HRQoL). The significant relationship between patient activation and HRQoL implies that patients with breast cancer who are able to actively participate in managing their health and health care are more likely to have higher HRQoL. Interventions that aim to improve HRQoL in patients with breast cancer could target modifiable factors like patient activation.